STRATEGI KOMUNIKASI DINAS LINGKUNGAN HIDUP DAN KBERSIHAN KOTA PEKANBARU DALAM MENSOSIALISASIKAN AKSI PEKANBARU BERSIH - Rani Nofri Angraini; Evawani Elysa Lubis (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Pekanbaru is the capital of Riau Province, which has experienced an increase in population every year, this population growth has resulted in an increase in the amount of waste generated by its people. The Aksi Pekanbaru Bersih is one of the activities involving the entire Pekanbaru City community with the aim of creating a clean, healthy, safe, comfortable and beautiful Pekanbaru City based on Regional Regulation No.8 of 2014 with sanctions for violators. Socialization is one way of informing and inviting the public to follow the applicable regulations, in socialization of course requires the right communication strategy so that optimal communication goals can be realized. The purpose of this study was to determine the communication strategy of Dinas Lingkungan Hidup dan Kebersihan Kota Pekanbaru in socializing the Aksi Pekanbaru Bersih.This study uses a qualitative method. The technique of determining the research subject uses purposive technique in determining informants. There were 14 informants in this study, namely the Head of the Capacity Building, Information and Communication Environment Section, the Head of the Law Enforcement Section, Heads of the Village and communities. The data collection techniques used were interviews, observation and documentation. Miles and Huberman's interactive data analysis techniques. To achieve the validity of the data in this study, researchers used participation extension and triangulation. Based on the results of research to identify the first problem are the communicator strategies in the socialization of the Aksi Pekanbaru Bersih, namely the sub-sector of Capacity Building, Information and Environmental Communication and the sub-sector of Law Enforcement. The strategy for determining the audience is the sub-district, sub-district, RT / RW, school and university as well as the entire community of Pekanbaru City. Communication messages delivered are in the form of informative and persuasive messages with language that is easy to understand. The media used are print media, electronic media, online media, outdoor media and social media. Then related to the effects of this socialization, people only experience changes in knowledge and have not seen changes in behavior from the community. Keyword : Communication Strategy, socialization, Pekanbaru City